Statistik Data Administrasi Sensus Data Pasien Raat Inap Di RSE Medan - Bernad Julvian Zebua; Br P.A, Lea Sri Ita (Yayasan Literasi Sains Indonesia, 2022)
The daily census of inpatients is the number of inpatients starting at 00.00 to 24.00. In its implementation at RSE Medann involving nurses and data processing officers in the medical record section. However there are problems with medical record officers, completeness of data, effectiveness data processing, and timeliness of information presentation. The purpose of this study is to evaluate data management activities daily census of inpatients per day at the Medan RSE. This research is a descriptive study with quantitative and qualitative approaches, with the objects of daily census data management activities being inpatients, nurses, medical records officers, heads of medical records installations, and heads of inpatient rooms as subjects. Data were collected using questionnaires and checklists, analyzed by quantitative and qualitative analysis. From the results of the study, it is known that the inpatient data information in each room is incomplete, which will affect the effectiveness of data processing. It is concluded that this error occurs from two sides, namely the input side and the output side. On the input side, namely the education of medical record officers is not appropriate, data is incomplete on the length of care, age, debtor, diagnosis, recapitulation has not been completed, from the output side within one month the information cannot be known in the following month. It is hoped that there will be standard operating procedures and computer-based medical record systems.